Calculating environmental flows: Safeguarding the future of rivers and livelihoods - Eriyagama, Nishadi (CGIAR System Organization, 2023)
Across the globe, river flows are being altered by human activity, such as water extraction and diversion, and the construction of dams. At the same time precipitation is becoming more erratic as climate change accelerates, leading to shifting rainy seasons, prolonged drought, and intense flooding.